NMR measurement of small-molecule diffusion in PVA hydrogels: a comparison of CONVEX and standard PGSE methods - Regan, David G.; Momot, Konstantin I.; Martens, Penny J.; Kuchel, Philip W.; Poole-Warren, Laura (Diffusion Fundamentals, 2006)
Hydrogels are biocompatible polymeric materials that are becoming increasingly important in biomedical applications, such as drug delivery and tissue engineering. Understanding of small-molecule diffusion in these systems is important in the contexts of controlled drug release; transport of nutrients (e.g., O2 and growth factors) into the gel; and transport of cellular waste out of the gel. In this work, the diffusion coefficient of the aromatic amino acid phenylalanine (Phe) in non-crosslinked and crosslinked poly(vinyl alcohol)(PVA)hydrogels was measured using two NMR diffusion methods, CONVEX and the standard pulsed-gradient spin-echo (PGSE). Pulsed field-gradient (PFG) NMR measurements provide the advantage of measuring the molecular selfdiffusion coefficient directly and without having to rely on the physical release of the solute, but are often difficult to perform in tissues and hydrated polymers due to a large water signal. CONVEX is a recently proposed diffusion method that alleviates this problem by means of NMR excitation-sculpting water suppression. In the measurements presented here, CONVEX results were superior to those from PGSE measurements with respect to every test applied, and enabled a reliable comparison of the diffusion coefficients of Phe in crosslinked and non-crosslinked hydrogels. The value of D(Phe) was smaller in the non-crosslinked hydrogel than in the crosslinked gel; this finding is discussed in the paper.